Do Binding Beat Nonbinding Agreements? Regulating International Water Quality. (September 2019) - Köppel, Martin; Sprinz, Detlef F.
Does the form of a multilateral agreement (MEA) by itself improve environmental performance? In particular, do legally nonbinding MEAs pose a rival to the effect of more traditional legally binding international agreements? Our theory builds on the legal and international regimes literatures and postulates that legally binding agreements (LBAs) have more benign effects on water quality than legally nonbinding agreements (LNBAs). We probe two operationalizations of the form of MEAs. First, we purely focus on the form: of legally binding versus legally nonbindings. Second, we combine the form of an agreement each with an index of precision and an index of delegation. The empirical focus is on upstream–downstream water quality in Europe during 1990 to 2007. Our regression analyses, regardless of specification, find that LBAs beat LNBAs and that LBAs with high degrees of precision and delegation beat the effect of any other configuration of agreements with respect to enhancing water quality.